Cardiovascular complications in COVID‐19 patients with or without diabetes mellitus. Issue 2 (25th December 2020) - Abe, Temidayo; Egbuche, Obiora; Igwe, Joseph; Jegede, Opeyemi; Wagle, Bivek; Olanipekun, Titilope; Onwuanyi, Anekwe
Abstract: Introduction: Coronavirus disease 2019 (COVID‐19) has become a major global crisis. Preliminary reports have, in general, indicated worse outcomes in diabetes mellitus (DM) patients, but the magnitude of cardiovascular (CV) complications in this subgroup has not been elucidated. Methods: We included 142 patients admitted with laboratory‐confirmed COVID‐19 from April 1st to May 30th 2020; 71 (50%) had DM. We compared baseline demographics and study outcomes between those with or without DM using descriptive statistics. Multivariate logistic regression was used to estimate the adjusted odds ratio for the study outcomes in DM patients, compared to those without DM, stratified by age, sex and glycaemic control. CV outcomes of interest include acute myocarditis, acute heart failure, acute myocardial infarction, new‐onset atrial fibrillation and composite cardiovascular end‐point consisting of all individual outcomes above. Result: Mean age was 58 years. The unadjusted rates were higher in DM patients compared to non‐diabetics for the composite cardiovascular end‐point (73.2% vs. 40.6% p < .0001), acute myocarditis (36.6% vs. 15.5% p = .004), acute heart failure (25.3% vs. 5.6% p = .001), acute myocardial infarction (9.9% vs. 1.4% p = .03) and new‐onset atrial fibrillation (12.7% vs. 1.4% p = .009). After controlling for relevant confounding variables, diabetic patients had higher odds of composite cardiovascular end‐point, acute heart failure and new‐onset atrial fibrillation. Abstract : In this study, we investigated cardiovascular complications in 142 COVID‐19 patients with versus without diabetes mellitus. Patients with diabetes mellitus were more likely to be older, have more comorbidities, and less likely to receive life‐saving medications. After adjusting for relevant comorbidities, the adjusted odds for composite cardiovascular endpoint, acute heart failure, and new onset atrial fibrillation were significantly higher among patients with diabetes mellitus.